HAK DAN KEWAJIBAN SUAMI ISTRI DALAM RUMAH TANGGA TALA’AH KITAB UQUDULUJAIN FI BAYANI HUQUQ AZ-ZAUJAIN KARYA SYEKH MUHAMMAD NAWAWI AL-BANTANI - Umar, Umar (Fakultas Agama Islam, 2021)
The book of Uqudulujain Fi Bayani Huquq Az-Zaujain is a famous book, especially among Islamic boarding schools which is familiarly called the yellow book, the book was written by a famous cleric and studied in Mecca, namely Sheikh Muhammad Nawawi Al-Bantani, he is one of the great scholars owned by the State of Indonesia who came from the province of Banten, he is also an Indonesian citizen who lives in Arabia. The book Uqudulujain Fi Bayani Huquq Az-Zaujain was written in 1294. Sheikh Muhammad Nawawi Al-Bantani said that this book is very important for people who want harmony in building a household based on the Qur'an and hadith. This book also teaches the procedures for building a household, the rights and obligations of husband and wife in the household, husband's etiquette towards his wife and wife's etiquette towards husbands, as well as picking up stories from the severity of the Prophet and his Companions, which are an inspiration to Muslims today. This research is library research. Then it has the aim of knowing the position of husband and wife in the book Uqudulujain Fi Bayani Huquq Az-Zaujain and to what extent the rights and obligations of husband and wife are regulated in the book Uqudulujain Fi Bayani Huquq Az-Zaujain by Sheikh Muhammad Nawawi Al-Bantani. This study uses library research with a qualitative approach and the nature of descriptive-analytic research, where the researcher tries to explain the existing material with the aim of finding facts (fact finding) followed by adequate analysis as an effort to find problem solving. Collecting data using library materials method through written texts and soft-copy editions as well as analysis using content analysis methods. Based on the results of the study, the researchers concluded that: (1) The Book of Uqudulujain Fi Bayani Huquq Az-Zaujain in regulating the rights and positions of husband and wife places the rights of the husband on a higher level than the wife. (2) Equality of rights and obligations of husband and wife in the book Uqudulujain Fi Bayani Huquq Az-Zaujain both husband and wife have noble obligations, the husband is the head of the family, the husband is obliged to provide for his wife, the wife as a housewife is obliged to manage household affairs with and husband and wife must love each other, be faithful and help each other. The wife's right to her husband is the right to get good treatment, to get teaching from her husband, to get protection from her husband, and to get proper food and clothing. Meanwhile, the wife's obligation to her husband is to obey his orders as long as it does not violate God's rules, protect the husband's property, respect the husband's family, and dress up to look beautiful according to the husband.